Fulfillment of the Constitutional Rights for Persons with Intellectual Disabilities in General Elections - Bambang Sumantri; Ane Nor Cahya Ilmiah; Salfanil Farizi (CV. Pustaka Parawali, 2024)
The purpose of this research is to examine the fulfillment of the constitutional rights of persons with intellectual disabilities against the fulfillment of constitutional rights as citizens in general elections that are not mentioned concerning their voting rights in regulations on general elections. the contribution of this research is to equalize the provision of legal certainty of the State to persons with intellectual disabilities in general election regulations. In writing research at this time, normative legal research methods are used, as well as various legal approaches such as statutory approaches, case approaches by examining court decisions, and concept approaches. The results of the research in this paper show that legal protection to people with disabilities with disabilities in general elections as voters also have equal or equal rights based on the Constitution, Human Rights Regulations, Regulations on the Ratification of the Convention on the Rights of Persons with Disabilities, Regulations on Persons with Disabilities that exist in the State of Indonesia, each of which provides legal protection related to the right to vote for people with disabilities with disabilities. However, persons with disabilities have not fully received legal protection in the general election regulations, resulting in conflicting norms, so the author provides a solution for testing the Election Law which is directly contrary to the rules that are equal as well as to the state constitution to the Constitutional Court to provide legal certainty in accordance with what is made an ideal by the state.